Role of Free Iliac Crest Flap in Foot and Ankle Reconstruction - Repo, Jussi Petteri; Barner-Rasmussen, Ian; Roine, Risto P; Sintonen, Harri; Tukiainen, Erkki (Journal of reconstructive microsurgery, 2016)
Background Reconstruction of extensive bone and compound defects in the foot and ankle is challenging. This cross-sectional study aimed to assess the outcomes of free iliac crest flap in foot and ankle reconstruction. Methods We retrospectively reviewed patient records and identified 13 cases with 1 osseous and 12 composite free iliac crest grafts for compound fracture (n = 3) or sequelae (n = 10) in the foot and ankle. We applied the visual analogue scale foot and ankle, the Oswestry disability index, and the 15D health-related quality of life (HRQoL) instruments. Results The average follow-up period was 3.9 years (range, 1.3-8.0 years). Four patients underwent early reoperations; venous and arterial reanastomosis (n = 1), minor wound revision (n = 2), or flap reconstruction due to partial necrosis of the skin island (n = 1). The median time to bone union was 23 months (range, 7-46 months). One permanent pseudoarthrosis occurred. One patient underwent late below-knee amputation due to chronic pain and functional impairment. One patient required flap reconstruction due to a late donor-site defect. Seven patients completed the questionnaires on an average of 14.7 years postoperatively (range, 2.0-26.9 years). Noted impairment of the donor site and of the reconstructed limb ranged from none to significant. Five (out of seven) patients had a HRQoL comparable to that of an age-standardized general population. Conclusions The free iliac crest flap is a feasible option for extensive compound fractures and bone-healing complications in the foot and ankle. It can also be used to achieve ankle arthrodesis when other techniques have failed and in patients at high risk for amputation.